IRON REMOVAL IN WASTE WATER USING EXPANDED POLYSTYRENE AS AN ARTIFICIAL MEDIA (Nigerian Journal of Technology, 2018)
This study focused on the use of Expanded Polystyrene as an artificial media for the removal of iron from raw water. The experimental set-up consisted of continuous flow process and the mechanism for iron removal was by adsorption. Water sample of initial concentration 5.5mg/l was stored in a 50l container situated at an elevation of 4.4m above the floor and was connected to a plastic transparent container which contained the filter media” Polystyrene”. The effects of adsorbent dosage, contact time, pH and temperature were studied. Results showed that adsorption capacity increased with time for the time range of 0.68-47.6mins investigated and slightly with an increase in temperature until 40oC when it began to decrease, suggesting favorable adsorption at medium temperatures. The results showed that the procedure was efficient in reducing iron concentration from 5.5mg/l to 3.5mg/l within contact time of 5minutes. Better efficiencies could be achieved at higher contact times. The use of EPS material would also offer an avenue for recycling polystyrene widely used in packaging of equipment. http://dx.doi.org/10.4314/njt.v37i3.38